ANALOGY OF HUMAN SPIRITUAL JOURNEY IN MANTHIQUT THAIR BASED ON SARTRE - Fauziyah Kurniawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The aim of this research is to determine the analogy forms of human spiritual journey in Manthiqut Thair’s compendium and it known as human existence which consisted of Jean Paul Sartre’s experential perspective. This research is qualitative descriptive method with a literature philosophy approach. Data source collection techniques in this research are reading and writing. Analyst used Miles and Huberman’s model analysis techniques to interpret the data. Those are data reduction, displayed data, and outcome. The result of this research shows that Fariduddin Attar represented the journey of birds toward Simurg such as human spiritual journey to God with three aspects. First is initial aspect; seeking Simurg that analogized as initial steps of human to travel their life spiritual, transmission aspect; pretext and complaints of birds along the road are as analog to examinations and trials along spiritual humas’s journey, and last aspect is; seeking Simurg is analogized as a sequence of attitudes that must be possessed by human in order “to meet” with God in their heart. While the forms of human existence found in the Manthiqut Thair’s compendium are structure of being-in-itself amount twenty data and structure of being-for-itself as much nineteen data.